2017
DOI: 10.1111/jcal.12213
|View full text |Cite
|
Sign up to set email alerts
|

Designing a technology‐enhanced flipped learning system to facilitate students' self‐regulation and performance

Abstract: In recent years, the flipped classroom has become prevalent in many educational settings. Flipped classroom adopts a pedagogical model in which short video lectures are viewed by students at home before class so that the teacher can lead students to participate in activities, problem-solving, and discussions. Yet the design or use of technology that employs planned instructional strategies with sustainable support of self-regulation is scant. We propose a technology-enhanced flipped language learning system (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 47 publications
10
95
1
6
Order By: Relevance
“…Other studies have shown the effects of ipped learning in metacognitive skills [40]. One main reason is that in this method, the residents have the authority to manage resources, pace, place, and time which makes them capable of self-regulation and performance [18,34,41]. In our study, we found that the residents were highly satis ed with their curriculum and uniquely interactive case-based discussion.…”
Section: Discussionsupporting
confidence: 48%
“…Other studies have shown the effects of ipped learning in metacognitive skills [40]. One main reason is that in this method, the residents have the authority to manage resources, pace, place, and time which makes them capable of self-regulation and performance [18,34,41]. In our study, we found that the residents were highly satis ed with their curriculum and uniquely interactive case-based discussion.…”
Section: Discussionsupporting
confidence: 48%
“…The collaborative methodology implemented through LMS with additional technologies will guide student learning processes and provide oriented feedback to processes [13]. This methodology is useful through automated and individualized resources, so that the help each student may need is available at any time [14]. Nevertheless, learning autonomy with an LMS is a related disadvantage, due to the need for continuous supervision of the LMS by the teacher.…”
Section: Self-regulation Learning and Advanced Learning Technologiesmentioning
confidence: 99%
“…The majority of students (89.8%) felt the quiz status icons helped them monitor their progress. The ability to monitor progress is an important part of self-regulated learning (Zimmerman, 2002) and students have been shown to be more self-regulated when they feel more autonomous in their learning (Sierens et al, 2009).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%